Droplet growth, Ostwald’s rule, and emergence of order in Fused in Sarcoma - Farkhad Maksudov; Mauro L. Mugnai; Laura Dominguez; Dmitrii E. Makarov; D. Thirumalai (Proceedings of the National Academy of Sciences, 2026)
The low-complexity domain of Fused in Sarcoma (FUS-LC) undergoes phase separation, forming a dense, liquid-like phase that gradually matures into an ordered, gel-like state over long-time scales. During the maturation process, specific regions of the FUS-LC sequence-core-1, core-2, and core-3-become structured, giving rise to nonpolymorphic fibrils. Coarse-grained simulations predict that kinetically the least stable fibril-like core-3 forms first while the most stable core-1 appears last, in accord with Ostwald’s rule of stages. The fibril structure of the C-terminal core-3, predicted using AlphaFold, shows that a β -strand appears in this region early during droplet formation and triggers FUS-LC assembly. Multichain simulations, which ensure the equality of the chemical potentials between the phases, show that the dense phase forms through nucleation and coarsening, resembling Ostwald ripening. The approaches developed here are broadly applicable and could help uncover assembly mechanisms in other intrinsically disordered proteins like TDP-43, which shares key features with FUS-LC.